2018
DOI: 10.1016/j.rmed.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function predicts mortality and hospitalizations in outpatients with heart failure and preserved ejection fraction

Abstract: The presence of airflow limitation or arterial hypoxemia identify a group of patients with HFPEF at higher risk of death or cardiovascular hospitalizations, respectively. Given that both airflow limitation and arterial hypoxemia are treatable, we propose that lung function should be routinely evaluated in the outpatient management of HFPEF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
(31 reference statements)
0
12
0
8
Order By: Relevance
“…In the Norwegian Heart Failure Registry of 4,132 HF patients, COPD was independently associated with a 19% excessive risk of mortality during a mean follow-up duration of 13.3 months [ 32 ]. In addition, Andrea et al further suggested that impaired pulmonary function was predictive of long-term mortality in a relative small population of 71 HFpEF patients [ 33 ]. While obstructive ventilation, rather than restrictive airflow pattern, was correlated with long-term survival in patients with HFrEF [ 34 ], Andrea et al also proposed that the presence of airflow limitation was a major prognostic factor for mortality and cardiovascular hospitalization in patients with HFpEF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Norwegian Heart Failure Registry of 4,132 HF patients, COPD was independently associated with a 19% excessive risk of mortality during a mean follow-up duration of 13.3 months [ 32 ]. In addition, Andrea et al further suggested that impaired pulmonary function was predictive of long-term mortality in a relative small population of 71 HFpEF patients [ 33 ]. While obstructive ventilation, rather than restrictive airflow pattern, was correlated with long-term survival in patients with HFrEF [ 34 ], Andrea et al also proposed that the presence of airflow limitation was a major prognostic factor for mortality and cardiovascular hospitalization in patients with HFpEF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of all the studies that have demonstrated a significant association between the presence of COPD and increased risk of adverse outcome in patients with heart failure [6, 912, 15, 16, 1820, 22] only three defined COPD using spirometry and heart failure using echocardiography or natriuretic peptide levels [6, 20, 22]; of these three studies, only one adjusted for natriuretic peptide levels and found an association between COPD and all-cause mortality or cardiovascular hospitalisation, but in a study of only 71 patients with HeFNEF [22]. Natriuretic peptide levels are powerful prognostic markers in patients with heart failure and may also be useful prognostic biomarkers in patients with COPD [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have reported increased mortality amongst patients with heart failure and COPD compared with either diagnosis alone have either come from highly selected trial populations of patients with HeFREF [9, 15, 19], patients admitted with acute heart failure [6, 11, 16], or have involved only short-term follow-up [10, 12, 20]. Up to half of patients with heart failure have a normal ejection fraction (HeFNEF) [23], but the prognostic significance of COPD amongst outpatients with HeFNEF has, so far, only been assessed in a small number of patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the cause of death in heart failure patients have reported that while the main causes of death in HFrEF patients were heart failure exacerbation and sudden death, non-cardiovascular death, including due to respiratory failure or infections of the respiratory system, were the main causes of death in HFpEF patients, apart from cardiovascular causes of death [5,6]. In general, the decline in respiratory muscle strength is associated with inefficient ventilation as a cause of dyspnoea [27], and with reduced pulmonary function [9,15], which is a known risk factor for heart failure and/or respiratory infection [28][29][30]. Therefore, in the present study, RMW worsened HFpEF patient prognosis because it can decrease pulmonary function that leads to respiratory complications and the incidence of cardiovascular events, even in the subgroup analysis stratified into the previously reported indicator of HFpEF.…”
Section: Interpretations Of Findingsmentioning
confidence: 99%